Protection for Sale: An Empirical Investigation - Goldberg, Pinelopi Koujianou; Maggi, Giovanni (American Economic Review, 1999)
The Grossman-Helpman "Protection for Sale" model, concerning the political economy of trade protection, yields clear predictions for the cross-sectional structure of import barriers. Our objective is to check whether the predictions of the Grossman-Helpman model are consistent with the data and, if the model finds support, to estimate its key structural parameters. We find that the pattern of protection in the United States in 1983 is broadly consistent with the predictions of the model. A surprising finding is that the weight of welfare in the government's objective function is many times larger than the weight of contributions.